PERANAN KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS HASIL AUDIT - NANIK PURNOMO, IMELDA (Universitas Katolik Widya Mandala Surabaya, 2012)
The subject of the thesis is concerned with the identification of the role of the competence and independence of the auditors on the quality of the audit. The aim is to clarify the role of the competence and independence of the on the quality of the audit. Competence and Independence is an attitude that should be owned by an auditor, where competencies include knowledge and experience, while the independence of an auditor is defensive in addressing the pressures that exist. Where has the second attitude, expected results of audit quality. Audit have a good quality if fair, impartial, and objective, and disclose in accordance with the true situation.